Rio de la Plata estuary response to wind variability in synoptic to intraseasonal scales: 2. Currents' vertical structure and its implications for the salt wedge structure - Simionato, C.G. (2007)
Fil:Simionato, C.G. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.